Enantioconvergent catalysis - Mohr, Justin T.; Moore, Jared T.; Stoltz, Brian M. (Beilstein Journal of Organic Chemistry, 2016)
An enantioconvergent catalytic process has the potential to convert a racemic starting material to a single highly enantioenriched product with a maximum yield of 100%. Three mechanistically distinct approaches to effecting enantioconvergent catalysis are identified, and recent examples of each are highlighted. These processes are compared to related, non-enantioconvergent methods.
Keywords: asymmetric catalysis; enantioselectivity; synthetic methods

Stereochemistry of Organic Compounds - Eliel, E. L.; Wilen, S. H.; Mander, L. N. (Wiley-Interscience, 1994)
See for a summary of the enantioconvergent synthetic strategy.

(untitled) - Newhouse, T.; Baran, P. S.; Hoffmann, R. W. (Chem. Soc. Rev., 2009)
See for a review dealing with assorted economies of synthesis.

(untitled) - Yoshida, N.; Ogasawara, K. (Org. Lett., 2000)

(untitled) - Pedersen, T. M.; Hansen, E. L.; Kane, J.; Rein, T.; Helquist, P.; Norrby, P.-O.; Tanner, D. (J. Am. Chem. Soc., 2001)

(untitled) - Liu, Q.; Ferreira, E. M.; Stoltz, B. M. (J. Org. Chem., 2007)

(untitled) - Noyori, R.; Ikeda, T.; Ohkuma, T.; Widhalm, M.; Kitamura, M.; Takaya, H.; Akutagawa, S.; Sayo, N.; Saito, T.; Taketomi, T.; Kumobayashi, H. (J. Am. Chem. Soc., 1989)

Stereochemistry of Organic Compounds - Eliel, E. L.; Wilen, S. H.; Mander, L. N. (Wiley-Interscience, 1994)
See for a discussion of double stereodifferentiation.

(untitled) - Mohr, J. T.; Ebner, D. C.; Stoltz, B. M. (Org. Biomol. Chem., 2007)
The, term “stereoablation” refers to the destruction of a stereogenic element of a molecule. The term derives from the Oxford English Dictionary definition for ablation: “the action or process of carrying away or removing; removal.” The use of stereoablative reactions in enantioselective synthesis has been highlighted.

(untitled) - Evans, D. A.; Aye, Y. (J. Am. Chem. Soc., 2007)
The three types of enantioconvergent catalysis highlighted in this work are not comprehensive of all possible mechanistic pathways for achieving enantioconvergent catalysis. Specifically, many reactions with intermediates bearing multiple stereocenters are not addressed. See for a representative example.

(untitled) - Akai, S. (Chem. Lett., 2014)

(untitled) - Applegate, G. A.; Berkowitz, D. B. (Adv. Synth. Catal., 2015)

(untitled) - Cohen, D. T.; Eichman, C. C.; Phillips, E. M.; Zarefsky, E. R.; Scheidt, K. A. (Angew. Chem., Int. Ed., 2012)

(untitled) - Hoyos, P.; Pace, V.; Alcántara, A. R. (Adv. Synth. Catal., 2012)

(untitled) - Marcos, R.; Martín-Matute, B. (Isr. J. Chem., 2012)

(untitled) - Pellissier, H. (Adv. Synth. Catal., 2011)

(untitled) - Pellissier, H. (Tetrahedron, 2003)

(untitled) - Blank, N. F.; Moncarz, J. R.; Brunker, T. J.; Scriban, C.; Anderson, B. J.; Amir, O.; Glueck, D. S.; Zakharov, L. N.; Golen, J. A.; Incarvito, C. D.; Rheingold, A. L. (J. Am. Chem. Soc., 2007)
And references therein.

(untitled) - Seeman, J. I. (Chem. Rev., 1983)
See for a review.

Catalytic Asymmetric Synthesis - Trost, B. M.; Lee, C. (Wiley-VCH, 2000)

Comprehensive Asymmetric Catalysis - Pfaltz, A.; Lautens, M. (Springer, 1999)

Comprehensive Asymmetric Catalysis, Supplement 2 - Paquin, J.-F.; Lautens, M. (Springer, 2004)

(untitled) - Krishnan, S.; Stoltz, B. M. (Tetrahedron Lett., 2007)

(untitled) - Ma, S.; Han, X.; Krishnan, S.; Virgil, S. C.; Stoltz, B. M. (Angew. Chem., Int. Ed., 2009)

(untitled) - Zuo, J.; Liao, Y.-H.; Zhang, X.-M.; Yuan, W.-C. (J. Org. Chem., 2012)

(untitled) - Liao, Y.-H.; Wu, Z.-J.; Han, W.-Y.; Zhang, X.-M.; Yuan, W.-C. (Chem. – Eur. J., 2012)

(untitled) - Xie, X.; Jing, L.; Qin, D.; He, W.; Wu, S.; Jin, L.; Lou, G. (RSC Adv., 2014)

(untitled) - Kainz, Q. M.; Matier, C. D.; Bartoszewicz, A.; Zultanski, S. L.; Peters, J. C.; Fu, G. C. (Science, 2016)

(untitled) - Zuo, Z.; Cong, H.; Li, W.; Choi, J.; Fu, G. C.; MacMillan, W. C. (J. Am. Chem. Soc., 2016)

(untitled) - Mohr, J. T.; Behenna, D. C.; Harned, A. M.; Stoltz, B. M. (Angew. Chem., Int. Ed., 2005)

(untitled) - Mohr, J. T.; Nishimata, T.; Behenna, D. C.; Stoltz, B. M. (J. Am. Chem. Soc., 2006)

(untitled) - Kalek, M.; Fu, G. C. (J. Am. Chem. Soc., 2015)

(untitled) - Vedejs, E.; Chen, X. (J. Am. Chem. Soc., 1997)
Parallel kinetic resolution was first defined by Vedejs, although the example was not enantioconvergent.

(untitled) - Delhi, J. R.; Gotor, V. (Chem. Soc. Rev., 2002)
See for a review of PKR.

(untitled) - Strauss, U. T.; Felfer, U.; Faber, K. (Tetrahedron: Asymmetry, 1999)
See for a review of enantioconvergent strategies using biocatalysis, including catalytic enantioconvergent methods.

(untitled) - Pedragosa-Moreau, S.; Archelas, A.; Furstoss, R. (J. Org. Chem., 1993)

(untitled) - Xu, W.; Xu, J.-H.; Pan, J.; Gu, Q.; Wu, X.-Y. (Org. Lett., 2006)
A single biocatalyst capable of enantioconvergent PKR of styrene oxide was reported, although the enantioselectivity is somewhat lower.

(untitled) - Kroutil, W.; Mischitz, M.; Faber, K. (J. Chem. Soc., Perkin Trans. 1, 1997)
And references therein.